(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: This paper envisioned examining the participation of women political leaders in the local decision-making organs in Tanzania. Specifically, the study aimed to examine the number of women represented in the study local government structures (LGSs), the motives behind women participating in the LGSs and the duration of service in the study LGSs. Design/Methodology/Approach: The study used a cross-sectional descriptive research design. A cluster sampling technique was used to obtain the study villages and Mitaa. Both quantitative and qualitative research approaches with different data collection methods were used. To collect quantitative data, questionnaires were administered to 390 household heads both men and women in the study villages/Mitaa, while qualitative data were gathered using an interview guide, Focus Group Discussion (FGD) and non-participant observation checklist. Quantitative data collected were analyzed and presented in tables and figures while the qualitative ones were thematically analyzed. Findings: The study revealed that the number of women’s participation in various local committees in the study of local government structures has increased by 50% (Dodoma City) and 30% (Bahi District). However, motives for women leaders’ participation are constrained by limited continuity of tenure in the political office. Therefore, suitable interventions are recommended to address the existing capacity gaps. Research Limitation: The study targeted to involve an equal number of men and women household heads in each study village and Mitaa, however in some villages it happened to have less number of women than men household heads. Practical implication: This study recommends that more spaces should be given to women to participate in local decision-making structures and hold seats to enhance gender equality in politics. Originality/Value: This study focuses on the gender parity framework in local politics. It brings an understanding to the various government departments, ministries responsible for women and other stakeholders regarding the opportunities available for women to participate in local politics.